Annual Reviewer Acknowledgement - Al-Shaibani, Dr. Ghayth (JOURNAL OF ADVANCES IN LINGUISTICS, 2019)
The Editorial team of the journal would like to thank the reviewers for their work in refereeing manuscripts during 2019.